TAILORED ENGLISH LEARNING: UNCONVENTIONAL PERSPECTIVES FROM ENGLISH TUTORS IN NON-FORMAL EDUCATION CONTEXT - Bagas, M Shofi; Romadhon, M Galuh Elga (UHN IGB Sugriwa Denpasar, 2026)
The development of individualized English learning programs plays a crucial role in enhancing effective English language teaching in informal educational settings, particularly in private tutoring institutions where learners often have diverse needs, goals, and learning paces. This research aims to explore the perspectives of English tutors who provide daily instruction in private tutoring institutions in Indonesia regarding the conceptualization, development, and implementation of personalized English learning programs. Specifically, the study investigates how tutors adapt curriculum content, teaching strategies, and assessment practices to accommodate individual learner characteristics in non-formal educational contexts. This study employs a qualitative research design to obtain an in-depth understanding of tutors’ experiences and professional practices. The participants consist of English tutors working in selected private tutoring institutions in Indonesia. Data were collected through semi-structured interviews, classroom observations, and document analysis of teaching materials and learning plans used by the tutors. The interview guide served as the main research instrument, supported by observation sheets and documentation checklists to capture curriculum-related practices in authentic teaching situations. The collected data were analyzed using thematic analysis, involving data reduction, coding, categorization, and interpretation to identify recurring themes related to curriculum development and individualized teaching practices. The findings reveal that tutors rely heavily on practical teaching experience, learner feedback, and collaborative discussions with colleagues when designing personalized learning programs. The study also highlights the importance of communication strategies and shared decision-making in supporting effective curriculum implementation. Furthermore, the research identifies several challenges faced by English tutors in unconventional educational environments, including limited institutional guidelines, varying student proficiency levels, and time constraints in curriculum adaptation. Establishing collaborative relationships among tutors, learners, and institutional stakeholders emerges as a key strategy for improving teaching experiences and enhancing the quality of curriculum design in informal educational settings. These findings contribute to the broader academic discussion on personalized learning approaches and curriculum development in non-formal education contexts.